Simulating Microwave Radiation of Pyramidal Horn Antenna for Plasma Diagnostics (Communications in Computational Physics, 2006)
Computational simulation of the radiating structure of a microwave froma pyramidal horn has been successfully accomplished. This simulation capability is developed for plasma diagnostics based on a combination of three-dimensional Maxwellequations in the time domain and the generalized Ohm's law. The transverse electricalelectromagnetic wave of the TE1,0 mode propagating through a plasma medium andtransmitting from antenna is simulated by solving these governing equations. Numericalresults were obtained for a range of plasma transport properties including electrical conductivity, permittivity, and plasma frequency. As a guided microwave passing throughplasma of finite thickness, the reflections at the media interfaces exhibit substantialdistortion of the electromagnetic field within the thin sheet. In radiating simulation,the edge diffraction at the antenna aperture is consistently captured by numerical solutions and reveals significant perturbation to the emitting microwave. The numericalsolution reaffirms the observation that the depth of the plasma is a critical parameterfor diagnostics measurement.